Studies of wintertime storms over the Tushar Mountains of Utah: final report to Utah Department of Natural Resources - Rogers, David C., author; Rauber, Robert M., author; Grant, Lewis O., author; Department of Atmospheric Science, Colorado State University, publisher (Colorado State University. Libraries, 1986)
Supercooled liquid water flux over the Tushar Mountains was estimated from three hour averages of the radiometer and rawinsonde observations. The amount of liquid water represented by this flux over the two-month project was 17,000 acre feet, or about 45 percent of the total annual runoff in the Beaver River watershed.
March 6, 1986.
Keywords: Winter storms -- Utah -- Tushar Mountains; Weather control -- Utah -- Tushar Mountains; Precipitation (Meteorology) -- Modification -- Utah -- Tushar Mountains